Peace Education: Peace Counselling Training (PCT) to Reduce Student Aggressiveness towards School Counsellors - Supriyanto, Agus; Eka Saputra, Wahyu Nanda (ASEAN Journal of Empowering Community, 2022)
Students' mental health is disrupted during the COVID-19 pandemic due to an unstable economy and unprepared education in online learning facilities. Aggression appears in students because of the students' internal and external impacts, so school counsellors need to be equipped with counselling strategies. A peace counselling training program (PCT) is an effort to provide school counsellors with skills in helping students reduce aggression with a peaceful character. Peace counselling is a strategy to form a peaceful mindset without violence on students. The purpose of the PCT program for school counsellors is the skills of school counsellors to apply peace counselling to reduce student aggression. The PCT program is implemented through group discussion forums, information provision, training, mentoring. The target of the PCT program is school counsellors in Indonesia by involving guidance and counselling teacher consultation organizations. Evaluation of the process and results of the PCT program through mentoring impacts reducing aggression as measured by the aggressiveness scale. The implementation of the peace counselling program through FGDs, information provision, training, and mentoring is evaluated in each activity as a process evaluation. The results of the FGD are the emergence of the problem of student aggression which is very urgent to be reduced. The result of the counselling activity is the counsellor's understanding of peace counselling with urgency in the perspective of religion and self of peace. Counsellors can have skills in the implementation of peace counselling with six stages. Peace counselling can apply to a set of individual and group counselling. Implementing the program decreases student aggression with an average initial condition of 65.59, down to 58.64. The conclusion is the peace counselling program can reduce student aggression. A peace counselling program can be applied as a strategy to reduce student aggression by school counsellors.